MOBILITAS SOSIAL WARGA PENDATANG DI KELURAHAN KALAMPANGAN KECAMATAN SABANGAU KOTA PALANGKA RAYA - Sriyana, Sriyana (JURNAL SOCIOPOLITICO, 2024)
Social mobility is considered as movement between social classes in a society which can cause a person's status to rise or fall. The purpose of this writing is to determine the characteristics of the social life of migrant residents of Kalampangan subdistrict related to demographic information and socio-economic information, as well as to determine the type or form of social mobility of migrant residents in Kalampangan subdistrict. This research is qualitative in nature. The research material consists of interview material, observations and questionnaires. This research data analysis is a descriptive analysis of the social mobility of immigrants, mobility factors and their influence are analyzed qualitatively, through data collection, then data reduction, then data presentation and data verification.The results of this research show that: (1) the type of horizontal social mobility can be classified as social mobility which takes the form of a massive change in status from farmers to informal workers and other small businesses. Social mobility is usually driven by young people, secondary education and the unmarried. (2) The driving factors for social mobility of immigrants are the economic conditions of the region of origin that are less supportive, motivation to look for work with a higher level of income. (3) The direct impact of social mobility of immigrants to Kalampangan Village is changes in habits to adapt to new environments and increased income, as well as improved quality of life.